Evaluasi Kebijakan Pengadaan Barang Dan Jasa Melalui Sistem Marketplace Digital Payment Di Kantor Pusat Direktorat Jenderal Perbendaharaan - Lestariyanto, Amin; As'ad, Muhammad (Abiwara : Jurnal Vokasi Administrasi Bisnis, 2024)
The process of procuring goods and services through the marketplace and digital payment system is carried out to meet the needs of goods / services at the Head Office of the Directorate General of Treasury which is carried out with a digitized process from ordering to payment. This study aims to evaluate policies as well as inhibiting factors and efforts that have been made related to the policy of procurement of goods and services through the digital payment marketplace system at the Head Office of the Directorate General of Treasury (transaction period 2019 to 2022). The research method used is descriptive qualitative conducted through interviews, direct observation/observation and literature study (documentation). Based on the results of the study, it shows that the policy of procurement of goods and services through the digital payment marketplace system at the Head Office of the Directorate General of Treasury has met the criteria of effectiveness, efficiency, adequacy, equity and accuracy even though it still needs to improve the responsiveness criteria so that this policy is more optimal by solving problems related to limitations where the service system is still segmented in each bank that owns the platform, the need for interoperability of the service system with the APBN financial management accountability system, and the need to manage inhibiting factors by re-improving regulations and business processes and improving the service system used.